Related-factors of social support for students’ physical activity in a network perspective - Naildo Santos Silva; Júlio Brugnara Mello; Paulo Felipe Ribeiro Bandeira; Jorge Mota; Adroaldo Cezar Araújo Gaya; Anelise Reis Gaya (Revista Brasileira de Atividade Física e Saúde)
This study investigates the relationship between social support and moderate to vigorous physical activity, as well as the possible relationships between social support and socioeconomic status, gender and body mass index. Cross-sectional study with a non-randomized sample of 71 students (boys and girls) aged 7 to 12 and their parents or legal guardians. Social support and socioeconomic status were assessed using validated questionnaires. Height and body mass measurements were used for the body mass index equation. Moderate to vigorous physical activity was measured by accelerometers. The associations between all variables were tested by a network analysis. Moderate to vigorous physical activity is negatively correlated with socioeconomic status, body mass index and a question from the social support questionnaire: “How many times in the last week have you watched your child be physically active?”. We observed a positive correlation between moderate to vigorous physical activity with gender and a question from the social support questionnaire: “How many times in the last week did you provide transport for your child’s physical activity?”. Thus, moderate to vigorous physical activity has a negative correlation with socioeconomic status, body mass index and the variable “parents sometimes observe their child to be physically active”, and parents who provide transportation for the child to practice physical activity. In future, it is import to consider the network analysis in the intervention studies to promote adolescents’ physical activity.